THERAPY FOR ALZHEIMER’S DISEASE - FOCUS ON LECANEMAB - Jońca, Mikołaj; Majchrowicz, Gabriela; Kurys, Natasza; Piekarska, Weronika; Litke , Szymon; Gołacka, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Alzheimer’s disease (AD) is a chronic, progressive neurodegenerative disorder and the leading cause of dementia worldwide, with prevalence increasing due to population aging. It is characterized by cognitive decline, functional impairment, and significant public health burden. Pathophysiology involves a complex interplay of amyloid-β (Aβ) accumulation, tau pathology and neuroinflammation. Despite extensive research, current pharmacological management of Alzheimer’s disease relies primarily on symptomatic therapies and does not alter the underlying neurodegenerative process. The aim of this review is to summarize the current state of knowledge on therapeutic strategies for AD, with particular emphasis on lecanemab, a recombinant humanized antibody characterized by their selectivity for soluble Aβ oligomers. We discuss its mechanism of action, clinical evidence from recent randomized controlled trials assessing its efficacy and safety. In this review, lecanemab is not only addressed in the context of established and widely used therapies but also alongside novel treatments currently being tested. Lecanemab represents a significant step towards disease-modifying therapy for AD as it reduces brain amyloid. Although the available results are promising, current evidence suggests that monotherapeutic interventions targeting a single pathological mechanism may be insufficient to completely stop or reverse disease progression underscoring the need for further research to optimize therapeutic outcomes.